Studies on the Anti-Heparin Activity of Serum - Holger-Madsen, T (Thrombosis and Haemostasis, 1962)
The anti-heparin activity of serum was investigated by adding serum to normal, platelet-poor plasma and determining the heparin thrombin time.BaSO4-adsorbed serum and serum from platelet-poor plasma proved to exert a considerably less marked anti-heparin activity than plain serum. Even in platelet-poor serum, adsorbed with BaSO4 some anti-heparin activity still remained, but by far the greater part of the original activity had disappeared. In some patients, in whom determination of the plasma heparin thrombin time has shown increased heparin resistance, the serum may also exert a greater anti-heparin activity than normal serum. In patients on anticoagulant therapy with phenylindanedione even a considerable lowering of the prothrombin-proconvertin plasma level did not entail any reduction in the anti-heparin activity of the serum as compared with normal serum.